MODULE DEVELOPMENT BASED ON REALISTIC MATHEMATIC EDUCATION (RME) DATA PRESENTATION MATERIALS ON HIGH SCHOOL (JURNAL LEMMA, 2022)
The background of this research by the limitations of teaching materials and learning that is still teacher-centered, especially on data presentation material. Problems related to the presentation of data are often encountered in the daily lives of students, but the material for presenting data in textbooks has not been linked to the daily lives of students. Linking learning materials with students' daily lives is able to help students understand data presentation material. The purpose of this research is to produce a valid and practical Realistic Mathematical Education (RME) based module on data presentation material. The type of research used is Research and Development with reference to the Plomp development model. The product developed is a module based on Realistic Mathematical Education (RME) on data presentation material. The instruments used are validation sheets, practical questionnaire sheets, and interview guidelines. The results of the validity show that the module based on Realistic Mathematical Education (RME) is already valid with a percentage of 78%. The results of the practicality test with mathematics teachers and students obtained a percentage of 89.756% with a very practical category. Based on the results of the study, it can be concluded that the module based on Realistic Mathematical Education (RME) is valid and practical to use in Data Presentation material at SMPN 1 Nan Sabaris, Padang Pariaman Regency.